Violencia política y novela peruana durante el segundo belaundismo: La danza inmóvil de Scorza, Historia de Mayta de Vargas Llosa y Los sentimientos de Luciano de Melvin Ledgard - de Lima, Paolo (2025)
This study analyzes how the political violence of the 1980s, particularly during the second government of Fernando Belaunde Terry (1980-1985), becomes evident in Peruvian narrative through three emblematic novels: La danza inmóvil (1983) by Manuel Scorza, Historia de Mayta (1984) by Mario Vargas Llosa, and Los sentimientos de Luciano (1985) by Melvin Ledgard. These works offer diverse perspectives and narratives on the internal armed conflict that shaped Peru during this period. The analysis highlights how the authors depict violence, armed struggle, and social tensions, as well as the country’s cultural and political transformations. The research underscores the contrast between Scorza’s realist and ironic approach, Vargas Llosa’s historical and dystopian reflection, and Ledgard’s more intimate and urban perspective.